Chemosystematic Evaluation of Some Nigerian Gossypium hirsutum L. Using Qualitative and Quantitative Phytochemical Analysis - MUHAMMAD MUAZU, DANZAKI; OBA TOYIN, MUSTAPHA; ABDULHAMID, ABDULKAREEM KHADIJA (Borneo Journal of Resource Science and Technology, 2021)
There is little information on the use of phytochemicals for the systematic study of variation and resolving relatedness in Nigerian Gossypium hirsutum species. Thus, there is a need to carry out detailed phytochemical studies of the plant leaves, which could be helpful in ascertaining their diversity and relatedness. The qualitative and quantitative phytochemical screening was conducted on 18 accessions of G. hirsutum using the established laboratory protocols. The findings of this study indicated the presence of tannin, alkaloids, proline, flavonoids, and saponin in all of the accessions that were grouped into two at 17% genetic distance, indicating 83% relatedness. However, phytosterol, terpenoids and glycosides were absent in three of the accessions, which were grouped at 48%. The phytochemical compositions were tannin (1.30-1.09 mg/100 g), flavonoid (1.60-1.16 mg/100 g, terpenoid (0.42-0.35 mg/100 g), alkaloid (1.47-1.11 mg/100 g), saponin (4.86-1.59 mg/100 g), glycoside (1.02-0.88 mg/100 g), proline (1.57-1.0 mg/100 g) and phytosterol (0.36-0.2 mg/100 g). The aim of this research was to determine the diversity and relatedness of G. hirsutum genotypes collected from different locations of Nigeria. In general, this study emphasises the use of plant chemicals for classification purposes.